STUDI LITERATUR: KUALITAS KIMCHI BERDASARKAN LAMA FERMENTASI - Madina H, Styla Britania Sarah Noor; Faujania, Dyva Mustika (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2024)
Kimchi is a vegetable-based food product made through a curing and fermentation process as a form of preservation method for the perishable nature of vegetables. During the fermentation process, the formation of lactic acid bacteria occurs which can change the characteristics of vegetables from their original characteristics. The method used in this research is a literature study through the PRISMA (Preferred Reporting Item for Systematic Reviews and Meta Analysis) data collection stage of relevant journals to summarize information and answer the questions and objectives of the research conducted. The data sources used in this study are 7 journals on kimchi making and the effect of kimchi fermentation duration published in the range of 2018-2023. The quality of kimchi as seen from vitamin C content, total lactic acid, ash content, fat, protein, color preference, aroma, and texture of kimchi is influenced by the length of fermentation, while the pH value, crude fiber, and taste acceptance of kimchi are influenced by salt concentration, fermentation time, and the interaction between the two factors. However, the fermentation time had no influence on the moisture content aspect of kimchi.